The Copyright Protection of Computer Software in the United Kingdom - Lai, Stanley (Bloomsbury Publishing (UK), 2000)
This work analyses the scope of copyright protection for computer software in the United Kingdom,and examines challenges for the future. The work presents the case for the adoption and application of infringement methodology emanating from the courts in the United States, resulting in a narrower scope of protection than is presently argued for by many UK academics, practitioners and judges alike. The work makes a careful evaluation of the efficacy of the various prevailing tests for infringement of copyright in software and their progenies, suggesting an improved formula and advocating the utility of limiting doctrines to assist in the determination of substantial similarity of particular non-literal software elements, user interfaces and screen display protection. The monograph also contains a detailed study of reverse engineering, copyright defences, permitted acts, database protection and the copyright-contract interface in the context of computer software, not omitting crucial discussions of the internet, digital dissemination and the impact of recent treaty and legislative initiatives on British copyright law. As such it will be an important resource for practitioners, lecturers and students alike.